Comparative genomics of Sarcoptes scabiei provide new insights into adaptation to permanent parasitism and within‐host species divergence. Issue 6 (5th October 2022) - Xu, Jing; Wang, Qianghui; Wang, Sen; Huang, Wanlong; Xie, Yue; Gu, Xiaobin; He, Ran; Peng, Xuerong; Wu, Shuangyang; Yang, Guangyou
Abstract: Sarcoptes scabiei is the causative agent of a highly contagious skin disease in humans and more than 100 mammals. Here, we reported the first chromosome‐level reference genome of S. scabiei isolated from rabbits, with a contig N50 size of 5.92 Mb, a total assembled length of 57.30 Mb, ∼12.65% repetitive sequences and 9333 predicted protein‐coding genes. The phylogenetic tree based on 1338 shared high‐confidence single‐copy orthologous genes estimated that the mammalian ectoparasite S. scabiei and the plant‐feeding mite Tetranychus urticae separated ∼340 million years ago. Both neighbour‐joining tree and principal component analysis of 20 mite populations isolated from four hosts (humans, pigs, dogs and rabbits) distributed in three countries (China, Australia and the USA) consistently supported genetic subdivisions according to host species rather than geographical location. The demographic history of S. scabiei reconstructed by multiple sequentially Markovian coalescent analysis suggested that S. scabiei isolated from rabbits, humans, dogs and pigs diverged ∼5000 years ago. Investigation of the homeobox ( Hox ) genes revealed that S. scabiei contains 8 of 10 canonical Hox genes that are present in the arthropod ancestor, and the absence of the Abd‐A gene may correlate with the long gap between their front and back legs. Comparative genomics demonstrated that genes specific to scabies mites were mainly enriched in nutrition digestive systems, whereas genes in the families that involved detoxification (cytochrome P450, carboxyl/cholinesterases and the ATP‐binding cassette transporter C group) were extremely contracted compared with that of other mites analysed in this study. Selective sweep analysis of mite populations from various pairs of two out of the four host species revealed that the strongest selective sweep signals were mainly enriched in cysteine‐type peptidase activity and apoptosis. The results provided clues for the mechanisms of S. scabiei adaptation to a permanent parasitic lifestyle and knowledge that would enable further control of this highly contagious skin disease.